THE INFLUENCE OF REACTIVE POWER AND DYNAMIC BALANCE ON THE CHANGE OF DIRECTION SPEED-PLANNED AGILITY - Fuad Babajić,; Edin Užičanin,; Erol Kovačević,; Amer Mećević, (Sport Scientific And Practical Aspects, 2025)
The aim of this work was to determine the influence of the reactive power and dyinamic balance on the manifestation of the planned agility, or the ability to quickly change the direction (COD) of movement in students. For the purpose of this study, male students (N = 36) were selected, second and third year of the Faculty of Physical Education and Sports, University of Tuzla. The results achieved on the dynamic balance assessment variables did not significantly contribute to the explanation of the results achieved on the criterion variable for assessing the planned agility. On the other hand, the elastic power of the lower extremities at a significant level explains a total of 19% of the variability of agility. Consequently, the result shown that the elasticstrenght contributes significantly to the explanation of the results achieved on the variables for assessing the planned agility in the T-Test, while the dynamic balance variables has not been demonstrated as a significant factor in the overall explanation results assessing of the motor component of student agility.